The environment as a “human family heritage”. Taking seriously legal technical terms - Riofrío Martínez-Villalba, Juan Carlos (Revista de Derecho, 2025)
This article argues that the natural environment should be understood in legal terms as the family heritage of humanity. Recognizing the environment in this way helps to resolve several doctrinal challenges in intergenerational justice and carries significant implications for both national and international law. Drawing on the biblical account of the cosmos given to Adam and Eve, and exploring parallels in Catholic social teaching, Roman law, Indigenous cosmologies, and modern international treaties, this study identifies a persistent yet under-developed legal logic that treats nature as an intergenerational patrimony. After delineating the concept of family heritage and outlining its key characteristics (such as collective ownership, purpose orientation, protection of essential goods, and public-order status), this article presents ten normative consequences. These include: applying a parental standard of environmental stewardship, prioritizing the protection of vulnerable family members, establishing a duty to preserve and enhance common wealth (the heritage), reframing the concept of private property, and expanding the international law principle of “common heritage of humanity”. This article concludes that, from a legal standpoint, how the environment should be treated as part of humanity’s family heritage.